Furthering Transmission Electron Microscopy of Covalent Organic Frameworks - Weare, Benjamin L (2023)
The transmission electron microscope (TEM) is a powerful instrument capable of a range of imaging, crystallographic, and spectroscopic measurements. As a result it has seen application to covalent organic frameworks (COFs), a class of polymer characterised by their porosity, high surface area, and tunable structures. However, examining the literature found a systematic low uptake of TEM for investigating COFs despite TEMs ability to provide nanoscale structural and elemental characterisation. Therefore to characterise COFs this thesis applies a range of TEM techniques including bright-field TEM (BF-TEM) imaging, selected area electron diffraction (SAED), electron energy loss spectroscopy (EELS), and energy dispersive X-ray spectroscopy (EDX). BF-TEM in particular was found to be invaluable for establishing crystallinity in samples with poor powder diffraction patterns. Two COFs, the novel cHBC-BDA-COF and the literature COF-5 were synthesised as a powder and as hybrids with a range of nanocarbon supports to facilitate investigation of COFs with TEM. In addition, matrix-assisted laser desorption ionisation mass spectrometry (MALDI MS) was applied as an analytical tool to COFs for the first time in order to investigate their structure and confirm that polymerisation had occurred. In order to put the TEM investigations of COFs on a firm theoretical footing a coarse-grained graph theoretical model was developed that predicts the TEM projections of COFs based on their fundamental topology: this gave rise to face-on (FO), side-on (SO), armchair (AC), and zigzag (ZZ) projections that were later experimentally confirmed in COF-5 and cHBC-BDA-COF. A stochastic graph model was made to investigate the presence of these features in more realistic structures and to investigate how to define when a crystalline structure has become amorphous. The experimental e-beam stability of cHBC-COF, pyrene-COF, and the non-COF polymer Bet-P-1 was investigated using this methodology. Overall this thesis develops a powerful holistic methodology combining modelling, TEM, and bulk measurements to investigate the structure and synthesis of COFs.